DESAIN SISTEM KAMUS ISTILAH KOMPUTER BERBASIS ANDROID (STUDI KASUS DI SMA MUHAMMADIYAH 4 KARTASURA) - Nisa Fitriani; dahLan Susilo; Astri Charolina (JURNAL GAUNG INFORMATIKA, 2019)
Information and Communication Technology (ICT) is one of the subjects is be taught in SMA Muhammadiyah 4 Kartasura. These subjects are learning about computer basic operations, computer software, computer hardware, CorelDraw graphic design, internet introduction, computer networks etc. In ICT subjects students use the package book as a learning support, in the book there are many computer terms in it. The many existing computer terms make some students have difficulty to understanding the subjects matter, because not all the computer terms are described in the package book. The purpose of this research is to build the dictionary applications of computer terms based Android. The design of application system using UML (Unified ModelingLanguage), applications manufacture using software programming Notepad + + and Eclipse, while for applications development using waterfall method and system testingusing five view method. The dictionary applications of computer term have generated consists of for main menu that is a list menu of terms, menu of guide, menu of about, and menu of school profiles are user friendly and very helpful to students in studying ICT subjects. Applications are tested on Android smartphones with the same specifications but different version of the operating system, Smartfren Andromax L from the nine tested features result in an average application load speed of two point three seconds, Samsung Galaxy Grand Prime from the nine tested features result in an average application load speed two point eight seconds, and Samsung Galaxy J5 from the nine tested features result in an average application load speed of two point six seconds and all features running well.